Ratio Analysis of Infrastructure Investments: a Case Study of the Municipalities and Communes of the Olsztyn County - Waldemar Kozłowski (Barometr Regionalny)
A fundamental aspect of infrastructure investments made by local authorities is the evaluation of their effectiveness. Considering their public character, infrastructural investments require more methodological sophistication to allow an assessment of a number of areas which have been ignored in previous analyses. This paper introduces a model for evaluating infrastructural investments based on select socio-economic ratios. The results of the research can be used by local authorities during investment planning and evaluation.